2015
DOI: 10.3414/me13-01-0081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Underlying Causes of Inter-expert Disagreement in Retinopathy of Prematurity Diagnosis

Abstract: SummaryObjective: Inter-expert variability in imagebased clinical diagnosis has been demonstrated in many diseases including retinopathy of prematurity (ROP), which is a disease affecting low birth weight infants and is a major cause of childhood blindness. In order to better understand the underlying causes of variability among experts, we propose a method to quantify the variability of expert decisions and analyze the relationship between expert diagnoses and features computed from the images. Identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Computer-based image analysis systems may be able to help us better understand the relationships of all of these factors to expert behavior. 11,14,45,46 Third, the implications of these findings are limited to the diagnostic discrepancy in plus disease diagnosis in a single posterior pole image, and do not address other ICROP categories (e.g. zone and stage), or peripheral vascular features, which can influence overall disease severity in the current ICROP classification scheme.…”
Section: Discussionmentioning
confidence: 95%
“…Computer-based image analysis systems may be able to help us better understand the relationships of all of these factors to expert behavior. 11,14,45,46 Third, the implications of these findings are limited to the diagnostic discrepancy in plus disease diagnosis in a single posterior pole image, and do not address other ICROP categories (e.g. zone and stage), or peripheral vascular features, which can influence overall disease severity in the current ICROP classification scheme.…”
Section: Discussionmentioning
confidence: 95%
“…Retinopathy of prematurity (ROP) is an ocular disease observed in infants with low birth weight, especially premature infants. The retinal blood vessels of the infant suffering from ROP develop abnormally [ 1 ], which affects sight and may even lead to blindness in severe cases, e.g., due to retinal detachment. ROP is treatable by laser photocoagulation if the diagnosis and treatment are timely [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 That said, numerous studies have shown that a variety of features beyond this standard definition may be considered by physicians while diagnosing plus disease. 12,33,38,43 To address this potential confounder for 12 of the 34 images, 3 experts were asked to re-classify all 34 of the original 2007 cropped images. The average score was not significantly different from their original 2016 gradings (2.60 vs. 2.67); however it was significantly more severe than the original 2007 scores (2.1).…”
Section: Discussionmentioning
confidence: 99%